LATTICE VARIATION AND MICROHARDNESS OF NaClx NaBry-x KCl 1-y MIXED CRYSTALS GROWN FROM AQUEOUS SOLUTION (International Journal of Food and Nutritional Sciences, 2022)
Mixed crystals of alkali halides find their application in optical, optoelectronics, and electronic devices. In the present study, ternary mixed crystals of NaClx NaBry-x KCl1-y were grown from the aqueous solution. The grown crystals were characterized by taking XRD and Vicker’s microhardness measurement. Lattice Parameters were determined from the X-Ray diffraction data by available method. The hardness number and work hardening coefficient were determined from the hardness value. The lattice parameter thus calculated obey Vegard’s law and the work hardening coefficients shows that the grown crystals belong to hard category material